Molecular characterisation of a novel citrus-infecting emaravirus, citrus emaravirus 1 - R. Bester; C. Gill; J.H.J Breytenbach; C. Steyn; H.J. Maree; G. Cook (Archives of Virology, 2025)
The application of high-throughput sequencing (HTS) has accelerated the discovery of novel viruses and the genome sequencing of poorly characterised viruses in fruit crops, revealing a greater complexity of plant viromes than previously understood. Here, we report the identification and genomic characterisation of a novel emaravirus, tentatively named "citrus emaravirus 1" (CiEV1), from Citrus limon leaves collected in the North West Province of South Africa. HTS analysis identified contigs corresponding to the four conserved emaravirus genomic segments (RNA1-RNA4), each encoding characteristic proteins: RNA-dependent RNA polymerase, glycoprotein, nucleocapsid, and movement protein. Comparison of terminal sequences and phylogenetic analysis suggest placing CiEV1 within clade D of the genus Emaravirus (family Fimoviridae ). To date, no association with symptoms has been identified. This is the first report of an emaravirus detected in citrus, expanding the known host range of the genus and contributing to the growing evidence of viral diversity in citrus. Further investigation is required to determine the epidemiological significance of CiEV1 in citrus orchards.

Seasonal occurrence and condition of leopard seals at an extralimital Sub-Antarctic Island - Michael D. Ross; Monica Leitner; W. Chris Oosthuizen; Marthán N. Bester; Rowan K. Jordaan; Michael D. Voysey; Everhard C. Conradie; Banele Dosi; Sean Evans; Kyle J. Lloyd; Zafar Monier; Jean Purdon; et al. (Polar Biology, 2025)
Leopard seals ( Hydrurga leptonyx ) occur mainly south of the Antarctic Polar Front, but immatures, in particular, seasonally move beyond this range during the austral winter and spring, typically under increased sea ice conditions. Extralimital occurrences of leopard seals can be observed at several sub-Antarctic islands where they haul out to rest. We present new records of leopard seal sightings at Marion Island, southern Indian Ocean, from 2006 to 2024 and discuss fluctuations in their seasonal and annual abundance (drawing on data collected since 1980) and body condition based on regular surveys. The eastern beaches at Marion Island were surveyed every 7–10 days while the western beaches were visited monthly. Observed leopard seals were photographed and given a body condition score based on the visibility of bony protrusions. From 2006 to 2024, we identified 35 presumed unique immature leopard seals between July and November, with a peak in September, all being immatures. Individuals to which we could assign body condition scores were either in good or excellent condition. This contrasted with the prevailing hypothesis that leopard seal body condition deteriorates with decreasing latitude. However, we could not determine whether this was because of an actual shift in body condition or because we used a different scoring system from other studies. We recommend adopting a standardised scoring system for visually estimating pinniped body condition and a global repository to monitor leopard seal haul-outs. As an apex predator, leopard seals may be important indicators in Antarctic and sub-Antarctic ecosystems, and monitoring changes in their distribution and body condition may indicate environmental and biological changes in these remote regions.

Discovery of a divergent apple stem pitting virus variant and development of an RT-PCR assay for improved detection in South African pear orchards - K. Bougard; H. J. Maree; R. Bester (Journal of Plant Pathology, 2025)
In this study, the prevalence and genome diversity of apple stem pitting virus (ASPV) in commercial pear orchards in South Africa were investigated. Leaves were collected from trees in two geographically distinct regions, representing six different pear cultivars covering 12 orchards. Total RNA was extracted and assayed for ASPV using RT-PCR. A subset of 18 samples was subjected to high-throughput sequencing (HTS) for a more detailed analysis. Bioinformatic analyses of the HTS data, led to the identification and sequencing of a divergent ASPV variant with 85.10% nucleotide identity to the closest ASPV match in GenBank (isolate 13TF179E, MZ148065.1). Additionally, the study reports the development and validation of an end-point multiplex RT-PCR assay capable of detecting all known pear ASPV variants in South Africa. The multiplex produces three distinct amplicons: one targeting actin for an internal control, one to broadly detect foveaviruses, and one specific to ASPV. The sequence analyses of known ASPV variants confirmed high sequence diversity within this species and emphasized the need to further investigate the relationship between ASPV isolates.

Effects of water quality and ozone dosing on reaction pathways and ozonation products on the example of tramadol- and venlafaxine N-oxide - Suman Kharel; Peter R. Tentscher; Kai Bester (Chemical Engineering Journal, 2024)

Tracking the foraging migrations of Marion Island southern elephant seals ( Mirounga leonina ) during their first year of life - Trevor McIntyre; W. Chris Oosthuizen; Marthán N. Bester; Mark A. Hindell; Ryan R. Reisinger; Cheryl A. Tosh; John van den Hoff; P.J. Nico de Bruyn (Marine Mammal Science, 2024)
The first year of life is critical for large mammals to acquire foraging and predator avoidance skills. Southern elephant seal ( Mirounga leonina ) pups wean at approximately three weeks of age and depart on their first foraging trips in midsummer, typically remaining at sea for three to four months before returning to their natal islands. We describe the foraging trips ( n = 29) of 16 underyearling southern elephant seals from sub‐Antarctic Marion Island and compare these with trips ( n = 152) of 94 older seals from the same population. While subadults (prebreeding age) and adult females (breeding age) displayed directional travel, underyearlings traveled in multiple directions from the island with no evidence of repeatability of travel directions within or between individuals and years. Maiden trips took longer to complete than subsequent trips during the first year of life, but we found no evidence for significant changes in other track metrics between the first three foraging trips. The comparatively inconsistent movement patterns of underyearlings suggest that foraging strategies of individuals are influenced by their learning and/or success during the first year of life and that individual level consistency in successful foraging strategies only become apparent in subsequent years.

Bioactive Peptides from African Yam (AVIAIMF and GPADPF) and Taro (NGDF and NGNW) Reveal Multifunctional Antidiabetic Effects Using Biochemical and Cellular Models - Mohammed Auwal Ibrahim; June Cheptoo Serem; Aliyu Dantani Abdullahi; Suleiman Aminu; Abubakar Babando Aliyu; Aliyu Muhammad Musa; Bashir Musa; Megan J. Bester; Anabella R. M. Gaspar (International Journal of Peptide Research and Therapeutics, 2023)

Pathogenicity and virulence of south African isolates of Venturia inaequalis - T. A. Koopman; J. C. Meitz-Hopkins; K. R. Tobutt; C. Bester; C. L. Lennox (European Journal of Plant Pathology, 2022)

Pest interceptions on imported fresh fruits into South Africa - Livhuwani R. Nnzeru; Phumudzo P. Tshikhudo; Bester T. Mudereri; Moleseng C. Moshobane (International Journal of Tropical Insect Science, 2021)

Application of DNA mini-barcoding reveals illegal trade in endangered shark products in southern Africa - TA Asbury; R Bennett; AS Price; C da Silva; M Bürgener; JD Klein; SN Maduna; N Sidat; S Fernando; AE Bester-van der Merwe (African Journal of Marine Science, 2021)

Complete genome sequence of ornithogalum virus 3 - I. Mostert; R. Bester; D. Aldrich; M. Visser; I. Gazendam; M. Cloete; H. J. Maree; J. T. Burger (Archives of Virology, 2021)

New Antidiabetic Targets of α-Glucosidase Inhibitory Peptides, SVPA, SEPA, STYV and STY: Inhibitory Effects on Dipeptidyl Peptidase-IV and Lipid Accumulation in 3T3-L1 Differentiated Adipocytes with Scavenging Activities Against Methylglyoxal and Reactive Oxygen Species - Mohammed Auwal Ibrahim; June C. Serem; Megan J. Bester; Albert W. Neitz; Anabella R. M. Gaspar (International Journal of Peptide Research and Therapeutics, 2020)

Tuber Storage Proteins as Potential Precursors of Bioactive Peptides: An In Silico Analysis - Mohammed Auwal Ibrahim; Megan J. Bester; Albert W. Neitz; Anabella R. M. Gaspar (International Journal of Peptide Research and Therapeutics, 2019)

Reproductive philopatry in a coastal shark drives age-related population structure - Juliana D. Klein; Aletta E. Bester-van der Merwe; Matt L. Dicken; Kolobe L. Mmonwa; Peter R. Teske (Marine Biology, 2019)

Quantitative trait loci (QTL) mapping of blush skin and flowering time in a European pear (Pyrus communis) progeny of ‘Flamingo’ × ‘Abate Fetel’ - Solomon M. Ntladi; Jan P. Human; Cecilia Bester; Jessica Vervalle; Rouvay Roodt-Wilding; Kenneth R. Tobutt (Tree Genetics & Genomes, 2018)

Vagrant leopard seal at Tristan da Cunha Island, South Atlantic - M. N. Bester; W. A. Bester; M. Wege; R. A. Schofield; T. A. Glass (Polar Biology, 2017)

Phylogeography of the pelagic fish Seriola lalandi at different scales: confirmation of inter-ocean population structure and evaluation of southern African genetic diversity - BL Swart; AE Bester-van der Merwe; SE Kerwath; R Roodt-Wilding (African Journal of Marine Science, 2016)

Trend changes in sympatric Subantarctic and Antarctic fur seal pup populations at Marion Island, Southern Ocean - Mia Wege; Marie‐Pierre Etienne; W. Chris Oosthuizen; Ryan R. Reisinger; Marthán N. Bester; P. J. Nico de Bruyn (Marine Mammal Science, 2016)
Recent pup population estimates of sympatric Subantarctic ( Arctocephalus tropicalis ) and Antarctic fur seals ( A. gazella ) at Marion Island are presented. Published pup population estimates of A. tropicalis (1995 and 2004) with an unpublished total island count in 2013, and annual counts on subsets of rookeries (2007–2015) were analyzed using a hierarchical Bayesian model. The pup population declined by 46% (95% credible interval CI : 43%–48%) between 2004 (mean = 15,260, CI : 14,447–16,169 pups) and 2013 (mean = 8,312, CI : 7,983–8,697), mirrored by a 58%–60% decline at rookeries counted annually (2007–2015). Population decline was highest at high‐density west and north coast rookeries, despite negligible change in female attendance patterns, pup mortality or median pupping date over the previous 25 yr. A better understanding of foraging behavior and its effects on reproductive success and survival in this A. tropicalis population is needed before we can attribute population decline to any external factors. In contrast, total island counts of A. gazella pups in 2007, 2010, and 2013, suggest that this population is still increasing although the annual intrinsic rate of population growth decreased from 17.0% (1995–2004, 744 pups) to 4.0% (2010–2013, 1,553 pups). The slowed growth of A. gazella is likely the result of saturation at the main rookery.

Multiple occurrences of king penguin (Aptenodytes patagonicus) sexual harassment by Antarctic fur seals (Arctocephalus gazella) - William A. Haddad; Ryan R. Reisinger; Tristan Scott; Marthán N. Bester; P. J. Nico de Bruyn (Polar Biology, 2015)

The diet of the subantarctic fur seal Arctocephalus tropicalis at Marion Island - A. B. Makhado; M. N. Bester; S. Somhlaba; R. J. M. Crawford (Polar Biology, 2013)

Tiletamine/zolazepam immobilization of adult post-moult southern elephant seal males - Horst Bornemann; P. J. Nico de Bruyn; Ryan R. Reisinger; Sabine Kästner; Maria E. I. Márquez; Trevor McIntyre; Marthán N. Bester; Joachim Plötz (Polar Biology, 2013)

Isolation and validation of microsatellite markers from a depleted South African sciaenid species, the dusky kob (Argyrosomus japonicus), by means of the FIASCO/454 approach - L. Mirimin; J. C. Ruiz Guajardo; J. Vervalle; Aletta Bester-Van der Merwe; S. Kerwath; B. Macey; P. Bloomer; R. Roodt-Wilding (Conservation Genetics Resources, 2013)

Complete nucleotide sequence of a new strain of grapevine leafroll-associated virus 3 in South Africa - R. Bester; H. J. Maree; J. T. Burger (Archives of Virology, 2012)

Refining instrument attachment on phocid seals - Iain C. Field; Robert G. Harcourt; Lars Boehme; P. J. Nico de Bruyn; Jean‐Benoit Charrassin; Clive R. McMahon; Marthán N. Bester; Mike A. Fedak; Mark A. Hindell (Marine Mammal Science, 2012)

Long distance breeding dispersal of a southern elephant seal - Ryan R. Reisinger; Marthán N. Bester (Polar Biology, 2010)

Vagrant Antarctic fur seals at Gough Island in 2009 - Marthán N. Bester; R. R. Reisinger (Polar Biology, 2010)

Antarctic fur seal predation on cephalopods at Marion Island - Ryan R. Reisinger; P. J. Nico de Bruyn; Pierre A. Pistorius; Marthán N. Bester (Polar Biology, 2010)

Goose barnacles hitchhike on satellite-tracked southern elephant seals - Ryan R. Reisinger; Trevor McIntyre; Marthán N. Bester (Polar Biology, 2010)

Leucistic southern elephant seal at Marion Island - Ryan R. Reisinger; N. Thomas Mufanadzo; P. J. Nico de Bruyn; Marthán N. Bester (Polar Biology, 2009)

Shifting trends: detecting environmentally mediated regulation in long-lived marine vertebrates using time-series data - Clive R. McMahon; Marthán N. Bester; Mark A. Hindell; Barry W. Brook; Corey J. A. Bradshaw (Oecologia, 2009)

First-year survival of southern elephant seals, Mirounga leonina , at sub-Antarctic Macquarie Island - Clive R. McMahon; Harry R. Burton; Marthan N. Bester (Polar Biology, 1999)